A Rare Case of Drop Metastasis along Lumbar Column of Glioblastoma Multiforme - Rafaela Jucá Lindner; Frederico de Lima Gibbon; Guilherme Pitol; Guilherme Gago; Antônio Delacy Martini Vial; Marcelo Paglioli Ferreira (Brazilian Neurosurgery)
Glioblastoma Multiforme (GBM) is a malignant primary brain tumor. Drop metastasis is an intradural extramedullary spinal lesion that originates from an intracranial site. It is rare to have the incidence of drop metastases in a patient diagnosed with Glioblastoma Multiforme. We present and discuss a case report on a 35-year-old patient treated for GBM who presented drop metastases after the surgical procedure.